Evaluation Of Psycho-Emotional Health Of Students Of University City In Siberia; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 35 : Research Paradigms Transformation in Social Sciences (RPTSS 2017) - Rodionova E. V. Elena Viktorovna; Konyukhova T. V. Tatiana Vasilievna; Kashpur V. Valeriya; Arlyapova P. Polina (2018, 2018)
Title screen